1983
DOI: 10.1038/304749a0
|View full text |Cite
|
Sign up to set email alerts
|

The glucocorticoid receptor binds to defined nucleotide sequences near the promoter of mouse mammary tumour virus

Abstract: Glucocorticoids are known to induce the transcription of integrated proviral mouse mammary tumour virus (MMTV) genes in a variety of cell lines derived from mouse mammary tumours. Chimaeric genes in which selectable markers are linked to the long terminal repeat (LTR) region of MMTV can be induced by the synthetic glucocorticoid dexamethasone after introduction into mouse fibroblasts. This suggests that the regulatory elements required for hormonal induction are located within the cloned LTR fragments. The ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
286
1
3

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 620 publications
(305 citation statements)
references
References 19 publications
13
286
1
3
Order By: Relevance
“…Experiments with LTR deletion mutants showed that the receptor binding region was restricted to a DNA segment located between 202 and 50bp upstream from the cap (i.e. initiation) site (Scheidereit et al, 1983). It is precisely within this segment that one finds the GRE defined by the transfection experiments discussed above.…”
Section: Glucocorticoids Modulate Mrna Concentrationmentioning
confidence: 97%
See 2 more Smart Citations
“…Experiments with LTR deletion mutants showed that the receptor binding region was restricted to a DNA segment located between 202 and 50bp upstream from the cap (i.e. initiation) site (Scheidereit et al, 1983). It is precisely within this segment that one finds the GRE defined by the transfection experiments discussed above.…”
Section: Glucocorticoids Modulate Mrna Concentrationmentioning
confidence: 97%
“…Recent experiments with the chimaeric metallothionein-thymidine kinase constructs described above showed that the purified rat receptor binds preferentially to, and protects against nuclease digestion, a DNA sequence (-248 to -263) located within the GRE. This sequence has a high degree of homology with two regions (-186 to -170 and -129 to -1 13) of the MTV-LTR that are protected against nuclease digestion (Scheidereit et al, 1983). A comparison of these segments yields the consensus sequence T(C)GGTA(T)CAA(C)A(T)TGTT(C)CT.…”
Section: Glucocorticoids Modulate Mrna Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…While steroids like progestins and androgens have recently been shown to also affect MMTV transcription in mammary cells (11,12,13,14,15), it is the response to glucocorticoids in cultured fibroblasts that has been studied in greatest detail (16,17,18,19). In vitro binding of purified glucocorticoid receptor to MMTV DNA has been demonstrated, showing several binding sites within the glucocorticoid regulatory region (20,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…B (distal) and C (proximal): sequence of regulatory regions and mutants therein (coding strand). Below the wild-type sequence (7), two lines indicate the DNase I footprints (on both strands) of purified glucocorticoid receptor (20). Triangles (open for protection, filled for enhancement) point to residues involved in methylation protection experiments, and squares to residues involved in methylation interference (22).…”
Section: Introductionmentioning
confidence: 99%